Sikap Nasionalisme di SD YPPK Santo Thomas Aquino Nohotif: Kajian Kualitatif Terhadap Pemahaman dan Implementasi - Bertolomeus Belang; Dewa Bagus Sanjaya; I Nengah Suastika³ (Jurnal Ilmu Sosial dan Humaniora, 2025)
This study aims to examine the understanding and implementation of nationalism attitudes at SD YPPK Santo Thomas Aquino Nohotif through a qualitative descriptive-analytical approach. Research subjects included grade IV-VI students, teachers, principals, parents, and community leaders. Data were collected through participatory observation, in-depth interviews, Focus Group Discussions (FGD), and documentation, then analyzed using Miles and Huberman's interactive model. The findings reveal that students' understanding of nationalism remains conceptual and has not reached an optimal implementation level. Students can identify national symbols but have not deeply understood the meaning of national values. The implementation of nationalism attitudes is still limited to formal activities such as flag ceremonies and national holiday commemorations, not yet integrated into daily life. Factors influencing nationalism attitude formation include internal school aspects (learning quality, teacher competence, facilities), external factors (family support, community environment), technology and media factors, and socio-cultural factors. The main obstacles faced include pedagogical, infrastructural, socio-cultural, and economic limitations. This study recommends the need for more comprehensive, contextual, and sustainable nationalism cultivation strategies by integrating local values in national character education.